An appetite for wonder : the making of a scientist, a memoir - Dawkins, Richard, 1941- (Ecco Press, 2013)
Famous for his radical new vision of Darwinism, Richard Dawkins paints a colorful, richly textured canvas of his early life from innocent child to charismatic world-famous scientist.